Colonization of Burn Wounds and Susceptibility of Bacterial Isolates - Ana Kaftandjieva; Mare Stefkovska; Ema Ivanovska; Zhaklina Cekovska (Bulgarian Society for Microbiology, 2019)
Aim: To assess the time related changes in micro flora in burn wounds in our setting and to determine the susceptibility pattern to commonly used antibiotics. Material and methods: In a period of 8 months a total of 90 burn wound samples (swabs) from 23 hospitalized patients at the Burn Unit were sent for microbiological examination. Swabs were taken weekly in a period of four weeks or until the patients were dismissed from the hospital. Isolation, identification of bacteria and the determination of the antimicrobial susceptibility were according to standard microbiological techniques. Results: In the first and second week of hospitalization the predominant organism was Acinetobacter spp. By the end of the third week, P. aeruginosa had become more predominant. In a period of four and more weeks of hospitalization, 7 samples from two patients were positive (yielding double and triple isolates) with further prevalence of Acinetobacter spp. Most of Gram negative isolates were multidrug resistant. Acinetobacter spp isolates were resistant as follows: 100% to amoxicillin-clavulanic acid and to cephalosporins, 86,4% to cefepime, 91% to both amynoglycosides, 88,6% to ciprofloxacin and co-trimoxazole and 84% to piperacillin/tazobactam and carbapenems. Pseudomonas aeruginosa isolates were resistant as follows: 100% were resistant to AMC, cefuroxime and cefixime, 95% to cotrimoxazole, from 9% to 40% to cephalosporins, 13,6% to gentamicin, 9% to ciprofloxacin and 4,5% to amikacin and carbapenems. Conclusion: Knowledge of the responsible bacterial flora of burn wounds, its prevalence and bacterial resistance, is of crucial importance for fast and reliable therapeutic decisions.
Keywords: Burn Wound; Colonization; wound swabs; Acinetobacter spp; Pseudomonas aeruginosa